Paeoniflorin protects PC12 cells from oxygen-glucose deprivation/reoxygenation-induced injury via activating JAK2/STAT3 signaling - Zhang, Zhuo (Exp Ther Med, 2021)
Ischemic stroke is the most common type of stroke, and it has become a major health issue as it is characterized by high mortality and morbidity rates. Paeoniflorin (PF) is a natural compound and the main active ingredient of Radix Paeoniae. The aim of the present study was to investigate the role of PF in oxygen-glucose deprivation/reoxygenation (OGD/R)-induced injury of PC12 cells and its association with the Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathway. An in vitro model of OGD/R injury was established in PC12 cells. Subsequently, Cell Counting Kit-8 assay and ELISA were used to evaluate cell viability and the secretion of inflammatory factors, respectively, in PC12 cells subjected to OGD/R and treated with PF. The levels of oxidative stress indicators and inflammatory factors were measured using corresponding commercial kits. In addition, the apoptosis rate of PC12 cells subjected to OGD/R and treated with PF was determined by flow cytometry, and the expression of apoptosis-related proteins was analyzed by western blotting. Additionally, the expression levels of JAK2/STAT3 pathway-related proteins were also evaluated. The cell viability, levels of oxidative stress, inflammation and apoptosis were also measured in OGD/R-induced PC12 cell injury models following co-treatment of cells with PF and FLLL32, a specific inhibitor of JAK2/STAT3 signaling. Cell viability was reduced, while oxidative stress and inflammation were increased after OGD/R-induced injury. However, the treatment of cells with PF significantly enhanced cell viability, and alleviated oxidative stress, inflammation and apoptosis of OGD/R-treated PC12 cells. Furthermore, PF activated the JAK2/STAT3 signaling pathway. Following FLLL32 intervention, the effects of PF on oxidative stress, inflammation and apoptosis of OGD/R-treated PC12 cells were reversed. In conclusion, the findings of the present study suggested that PF may protect PC12 cells from OGD/R-induced injury via activating the JAK2/STAT3 signaling pathway, thus providing novel insight into the mechanism through which PF may alleviate ischemic stroke and indicating a potential strategy for ischemic stroke treatment.